Conjugated polymers based on 1, 8‐naphthalene monoimide with high electron mobility. Issue 3 (27th October 2017) - Zhu, Guomin; Zhang, Youdi; Hu, Yu; Zhao, Xiaohong; Yuan, Zhongyi; Chen, Yiwang
ABSTRACT: 1, 4, 8, 9‐Naphthalene diimides (NDIs) with strong electron accepting ability and high stability are excellent building blocks for semiconductor polymers. However, 1, 8‐naphthalene monoimide (NMI) with similar structure and energy levels as that of NDI has never been used to construct conjugated polymers because of synthetic difficulty. Herein, 3, 6‐dibromo‐NMI (DBNMI) with bulky alkyl groups was obtained effectively in a four‐step synthesis, and three donor‐acceptor (D‐A) type conjugated polymers based on NMI were firstly prepared. These polymers have strong absorption in the range of 300–600 nm, low LUMO level of 3.68 eV, and moderate bandgaps of 2.18 eV. Space charge limiting current measurements indicate these polymers are typical electron transporting materials, and the highest electron mobility is up to 5.8 × 10 −3 cm 2 V −1 s −1, which is close to the star acceptor based on NDI (N2200, 5.0 × 10 −3 cm 2 V −1 s −1 ). © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 276–281 Abstract : 3, 6‐Dibromo‐NMI with bulky alkyl groups was obtained effectively in a four‐step synthesis, and three donor‐acceptor (D‐A) type conjugated polymers based on NMI were prepared. SCLC measurements indicate that these polymers are typical electron transporting materials, and that the highest electron mobility is up to 5.8 × 10 −3 cm 2 V −1 s −1 . This is close to the star acceptor based on NDI (N2200, 5.0 × 10 −3 cm 2 V −1 s −1 ).